(untitled) (REMUNOM, 2025)
This article aims to investigate the reasons that lead to the judicialization of the Continuous Installment Payment (BPC), which is listed in article 203, item V of the 1988 Constitution of the Federative Republic of Brazil and was subsequently instituted by the Organic Law of Social Assistance (LOAS). Its eligible target audience is people with disabilities who have restrictions on independent living and elderly people from sixty-five years of age onwards who are unable to provide for their own sustenance or through their family. Despite being a social right, this benefit is not being accessed by the target audience due to administrative denial by the social security agency managing the benefit, which adopts administrative procedures that hinder and limit its granting. In this sense of restriction of social rights, the Brazilian context of the judicialization of social policies is a growing phenomenon in the field of Social Security, and the main obstacles to granting that culminate in the judicialization of this social right will be discussed. The study will be conducted through a literature review based on the contributions of consulted authors, combined with an analysis of the evolution of benefits that were litigated between 2020 and 2025, as demonstrated on the website of the National Council of Justice (CNJ). It is preliminarily noted that, due to current errors in the targeting of Social Security policy, tens of thousands of eligible individuals are administratively prevented from accessing benefits and seek resolution of the conflict through the judiciary.